Invariant Natural Killer T lymphocytes as natural sensors for microbes: a two-edged sword in liver diseases - Gonzatti, Michelangelo Bauwelz; Keller, Alexandre Castro (Frontiers in Immunology, 2025)
The liver is a complex immunological organ characterized by a dual blood supply from the hepatic artery and portal vein, which continuously exposes it to microbial and dietary antigens, as well as potential pathogens that gain access to the circulation. This characteristic renders the liver particularly susceptible to immune activation, which may disrupt hepatic homeostasis and promote inflammation, thereby contributing to the pathogenesis of various liver diseases. Invariant natural killer T (iNKT) cells, a subset of liver-resident T lymphocytes, act at the intersection of hepatic immune surveillance and inflammatory responses. These cells are capable of rapid activation in response to glycolipid antigens presented by CD1d molecules and a broad range of pro-inflammatory stimuli, including cytokines and damage-associated molecular patterns. Perturbations in the intestinal barrier or dysbiosis of the gut microbiota can exacerbate hepatic exposure to microbes and metabolites, amplifying inflammatory signaling within the liver microenvironment. Although mouse models do not fully capture the complexity and heterogeneity of human liver diseases, the conserved nature of iNKT cell responses across species makes them useful for study their potential roles in human pathology. Furthermore, the discovery of specific iNKT agonists with polarizing ability emerges as an alternative to modulate the inflammatory microenvironment and the progression of hepatic damage. Therefore, a comprehensive understanding of iNKT cell dynamics under both physiological and pathological conditions is essential for the development of targeted therapeutic strategies to prevent or mitigate inflammatory liver diseases.